Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1103/physrevb.99.144505
|View full text |Cite
|
Sign up to set email alerts
|

Nanobridge superconducting quantum interference devices: Beyond the Josephson limit

Abstract: Nano-scale superconducting quantum interference devices (nano-SQUIDS) where the weak-links are made from nano-bridges -i.e., nano-bridge-SQUIDs (NBSs) -are one of the most sensitive magnetometers for nano-scale magnetometry. Because of very strong non-linearity in the nanobridge-electrode joints, the applied magnetic flux (Φa) -critical current (Ic) characteristics of NBSs differ very significantly from conventional tunnel-junction-SQUIDs, especially when nanobridges are long and/or the screening parameter is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…However, improvement of spatial resolution is still a challenging task. The apparent solution of this limitation seems to be a decrease in the geometrical dimensions of the SQUID [8][9][10][11][12]. It is the essential reason why SQUIDs of nanoscale dimensions attract the interest and efforts of numerous groups worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…However, improvement of spatial resolution is still a challenging task. The apparent solution of this limitation seems to be a decrease in the geometrical dimensions of the SQUID [8][9][10][11][12]. It is the essential reason why SQUIDs of nanoscale dimensions attract the interest and efforts of numerous groups worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report the development of a batch fabrication process for SOC by taking advantage of the robustness of 3D nano-bridge junctions 23,24,25 so that deep silicon etching 26,27 could be utilized. This step generated a sharp edge around the pick-up loop which enabled scanning in close proximity to the sample surface.…”
mentioning
confidence: 99%
“…From equation 2 and the second Josephson relation [38,39], it is clear that the j-th weak link behaves as an inductor with kinetic inductance L Kj = Φ0 2π ϕcj Icj , where Φ 0 is the magnetic flux quantum (see equation 1 and the electrical model in figure 1). For the typical lengths of the Dayem bridges explored in this work (approximately 150 nm), a linear CΦR represents a reasonable approximation in the explored low temperature range T T c [22]. Indeed, by solving the Ginzburg-Landau equations, it has been shown that for nanobridges longer than 3ξ(T ), the CΦR becomes multivalued and progressively more linear [19,40].…”
Section: Properties Of a Squid Containing Two Nominally Different Day...mentioning
confidence: 62%
“…Using this method, we conduct an experimental study of lithographically fabricated MoGe superconducting nanobridges and their current phase relation (CΦR). The latter is approximately given by [18][19][20][21][22]…”
Section: Introductionmentioning
confidence: 99%